The synthetic cannabinoids menace: a review of health risks and toxicity - Ayman Alzu’bi (13162392) (2024)
Synthetic cannabinoids (SCs) are chemically classified as psychoactive substances that target the endocannabinoid system in many body organs. SCs can initiate pathophysiological changes in many tissues which can be severe enough to damage the normal functionality of our body systems. The majority of SCs-related side effects are mediated by activating Cannabinoid Receptor 1 (CB1R) and Cannabinoid Receptor 2 (CB2R). The activation of these receptors can enkindle many downstream signalling pathways, including oxidative stress, inflammation, and apoptosis that ultimately can produce deleterious changes in many organs. Besides activating the cannabinoid receptors, SCs can act on non-cannabinoid targets, such as the orphan G protein receptors GPR55 and GPR18, the Peroxisome Proliferator-activated Receptors (PPARs), and the Transient receptor potential vanilloid 1 (TRPV1), which are broadly expressed in the brain and the heart and their activation mediates many pharmacological effects of SCs. In this review, we shed light on the multisystem complications found in SCs abusers, particularly discussing their neurologic, cardiovascular, renal, and hepatic effects, as well as highlighting the mechanisms that intermediate SCs-related pharmacological and toxicological consequences to provide comprehensive understanding of their short and long-term systemic effects. Other Information Published in: European Journal of Medical Research License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1186/s40001-023-01443-6